2013
DOI: 10.1186/1477-7819-11-10
|View full text |Cite
|
Sign up to set email alerts
|

Askin’s tumor: a case report and literature review

Abstract: Askin’s tumor is a primitive neuroectodermal tumor developing from the soft tissues of the chest wall. Its diagnosis approach is complex and requires a multidisciplinary team. Given the rarity of this entity, no regimen has been validated in the literature. We report two cases of Askin’s tumor with a major response to polychemotherapy and surgical resection in one case. These cases show that treatment of Askin’s tumor should be multimodal, requiring discussion in multidisciplinary tumor working groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 13 publications
(14 reference statements)
1
16
0
10
Order By: Relevance
“…Interestingly, this tumor localization, along with local rib and lung invasion observed in our model, is a characteristic of Askin tumors - a specific subgroup of primitive neuroectodermal tumors (PNET) [45, 46]. This thoracopulmonary localization of SK-ES1 metastases implicates specific biological features of tumor cells, which facilitate their growth in this particular region [45, 46]. Another characteristic feature of SK-ES1 tumors is their affinity for neural tissues, as manifested by the presence of brain and spine metastases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, this tumor localization, along with local rib and lung invasion observed in our model, is a characteristic of Askin tumors - a specific subgroup of primitive neuroectodermal tumors (PNET) [45, 46]. This thoracopulmonary localization of SK-ES1 metastases implicates specific biological features of tumor cells, which facilitate their growth in this particular region [45, 46]. Another characteristic feature of SK-ES1 tumors is their affinity for neural tissues, as manifested by the presence of brain and spine metastases.…”
Section: Discussionmentioning
confidence: 98%
“…Although rare, brain metastases are associated with a particularly poor outcome in ES patients and factors facilitating their formation remain unknown [3]. Given the unfavorable prognosis of Askin tumors (14% 6-year survival) and ES patients with secondary cerebral tumors, uncovering the mechanisms underlying such properties of ES subsets via our model may inform novel therapeutic approaches [45, 46]. …”
Section: Discussionmentioning
confidence: 99%
“…According to classification of tumors of the nervous system, Askin's tumor is a member of the Ewing's sarcoma family of tumors/peripheral PNETs. The clinical occurrence of Askin's tumor is rare and only a limited number of cases have been documented (6)(7)(8)(9)(10)(11). The present study reported 11 cases of Askin's tumor, a relatively large sample size in terms of its incidence rate.…”
Section: Discussionmentioning
confidence: 79%
“…Si existe alteraciones en el descenso tiroideo, se puede encontrar tejido glandular aberrante a lo largo del trayecto del conducto tirogloso. La ectopia tiroidea es un tipo de disgenesia con una prevalencia de 1:7.000, siendo más común en mujeres que en hombres con una relación 4:1 [3,4]. Se describen ectopias linguales, sublinguales, tiroglósicas e intralaringotraqueales, siendo las primeras las más frecuentes [5].…”
Section: Introductionunclassified
“…Se precisa realizar diagnóstico diferencial con hemangiomas, linfomas, fibromas, abscesos y tumores malignos de la lengua [7]. Casos de tiroides ectópica lingual son diagnosticados de forma incidental con métodos de imagen [3,6].…”
Section: Introductionunclassified